LITERATURE OF REVIEW THE INFLUENCE OF ENVIRONMENTAL SATISFACTION, JOB SATISFACTION AND BALANCE OF LIFE AND SALARY ON EMPLOYEE PERFORMANCE AT PT Bank Syariah Indonesia - Dewi Puspaningtyas Faeni; Riyan kusuma Ardhan (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
This research will explain the influence of employing a review of the literature to determine the effects of work satisfaction, balance of life, and environmental satisfaction on employee performance. Based on this research, four hypotheses need to be addressed. In order to make research decisions, this study used a quantitative design with numerical data. utilizing the statistical tools in SPSS, evaluating the viability of models and data, and responding to theories. One of the biggest banks in Indonesia, PT Bank syariah Indonesia TBK, is where this study was carried out.